Cervical ectopic pregnancy presented with massive life threatening haemorrhage: a case report - Medhi, Robin; Patel, Jatinkumar Vishnubhai; Mishra, Asmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Here we report a case of a cervical ectopic pregnancy presented with massive life threatening haemorrhage and its subsequent management. After an unsuccessful attempt to stop the bleeding with balloon catheter and vaginal tamponade, a total abdominal hysterectomy was performed, this is the procedure of choice for treatment of cervical pregnancy under conditions of urgency and life-threatening bleeding.